2012
DOI: 10.1016/j.urology.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of “Scarless” Surgery: A Critical Analysis of the Literature

Abstract: Evidence relating to the perception and view of patients and physicians on natural orifice transluminal endoscopic surgery (NOTES) and laparoendoscopic single-site surgery (LESS) was scrutinized. A comprehensive literature search was performed through PubMed. A total of 18 studies were included in the analysis. Patients demonstrated interest in scarless surgery, with a preference for LESS over NOTES. Safety and efficacy remain the key factors in the decision-making process of patients. With more information ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
(47 reference statements)
2
11
0
Order By: Relevance
“…In addition to safety and efficacy as the most important factors, the cosmetic consequences of a procedure are also important in surgical treatment decision making. This is especially true for younger patient groups [5,10].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to safety and efficacy as the most important factors, the cosmetic consequences of a procedure are also important in surgical treatment decision making. This is especially true for younger patient groups [5,10].…”
Section: Discussionmentioning
confidence: 98%
“…The number of novel surgical procedures performed is dictated by patient demand and their perception of the techniques. The establishment of a gold standard for one of the first intricate MIS procedures, laparoscopic cholecystectomy, was mainly driven by the public [5]. In addition to safety and efficacy as the most important factors, the cosmetic consequences of a procedure are also important in surgical treatment decision making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review on public perception of scarless surgery, Autorino et al [5] showed that safety and efficacy are as the primary surgical outcomes for patients while scar issue is such significant just when equivalence results and risks are assured. In a prospective comparative study, Porpiglia et al showed that patients who underwent minilaparoscopic pyeloplasty were significantly more satisfied with their cosmetic result than those who had standard laparoscopic approach [8].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this concept, novel surgical approaches such as natural orifice translumenal endoscopic surgery (NOTES) and laparoendoscopic single-site surgery (LESS) have been explored [5]. However, these techniques carry some limitations, including an unfavorable ergonomy and the lack of optimal instrumentation, are still under development.…”
mentioning
confidence: 99%